2023
DOI: 10.7759/cureus.49101
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness, Esthetics, and Success Rate of Dental Implants in Bone-Grafted Regions of Cleft Lip and Palate Patients: A Systematic Review and Meta-Analysis

Ankita Pathak,
Mithilesh M Dhamande,
Seema Sathe
et al.

Abstract: Congenital clefts impair function and appearance, thus impacting a patient's social and mental health. A multidisciplinary team that can offer comprehensive treatment from infancy through maturity and beyond can successfully address these abnormalities. Dental rehabilitation is very important for these patients; these abnormalities should be identified and must be treated accordingly. Hence it is of utmost importance to know the success rate and changes in quality of life from patient satisfaction in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…During the follow-up period, the patient showed good functional and aesthetic outcomes, and no problems were noted. These findings highlight the potential of basal implants as a workable and practical remedy for situations involving poor bone health, providing a possible substitute for conventional implant techniques [26][27][28].…”
Section: Discussionmentioning
confidence: 76%
“…During the follow-up period, the patient showed good functional and aesthetic outcomes, and no problems were noted. These findings highlight the potential of basal implants as a workable and practical remedy for situations involving poor bone health, providing a possible substitute for conventional implant techniques [26][27][28].…”
Section: Discussionmentioning
confidence: 76%
“…Individuals who have prominent buccal concavities on the lateral aspect of the maxillary sinus may be more susceptible to problems, particularly if they undergo non-guided surgery. This technique is clinically challenging due to the anatomical complexity of the structures and the complexities of the zygoma [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Following a 36-month follow-up, a systematic evaluation of research published between 2000 and 2012 found a 97.86% survival rate. The American College of Prosthodontists recognizes the adaptability of zygomatic implants in a range of therapeutic contexts, emphasizing their contribution to improving patients' quality of life and offering effective and dependable treatment alternatives [25][26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation